Industry strategies to market opioids to children and women in the USA: a content analysis of internal industry documents from 1999 to 2017 released in State of Oklahoma v. Purdue Pharma, L.P. et al - Dorie E Apollonio; Hanna Yakubi; Brian Gac (BMJ Open, 2022)
Objective Identify advertising strategies used to market opioids to women and children.Design Qualitative content analysis of internal pharmaceutical industry documents released in litigation, dated between 1999 and 2017.Setting USA.Participants Opioid manufacturers (Janssen, Ortho-McNeil, Purdue, Teva (Actavis), Janus, Cephalon); women; children.Primary and secondary outcome measures Advertising campaigns, industry executive statements regarding marketing goalsMethods We examined ((DATASET) link: https://www.industrydocuments.ucsf.edu/drug/) documents released in State of Oklahoma v. Johnson & Johnson (2019) to identify marketing strategies and campaigns developed by opioid manufacturers that focused on children and women, as well as public records, including websites developed by manufacturers and their allies, to confirm whether marketing campaigns proposed in internal industry documents were implemented. Documents identified as relevant were coded for themes based on expectations drawn from previous research on marketing using internal industry documents, which included making emotional appeals and understating the risks of addiction.Results We found that opioid manufacturers sought to recruit coaches and school nurses to encourage opioid use by children, developed unbranded initiatives suggesting adolescents ask providers for pain care medications, suggested that opioid use could reduce health risks associated with untreated pain among women and advocated to policy makers that women faced unmet needs for pain medication.Conclusions The USA strictly regulates direct marketing of medications but does not place the same restrictions on indirect marketing and unbranded campaigns, which encourage people to seek treatment without indicating the names of specific products. Opioid manufacturers in the early 21st century appear to have relied largely on unbranded campaigns for marketing, which they described externally as public health promotion and internally as a way to increase sales of opioids. The rapid increase in opioid use concomitant with these campaigns suggests that additional scrutiny of this kind of marketing may be needed in order to protect vulnerable groups.